Implementation of Total Productive Maintenance in a Jute Bag Industry:a Case Study - Haider, M M Nadim; Rafiquzzaman, Md (Journal of Engineering Science, 2023)
In this competitive world, manufacturing industries are suffering from several problems such as breakdown of machine, production adjustments, poor working of defective equipment, poor maintenance and management, unhealthy working area and this lead to low productivity, increasing wastage, fire damage and major losses in the company’s growth. Total Productive Maintenance (TPM) approaches can be promising solution to overcome these problems. Therefore, this study attempts to evaluate the contributions TPM initiatives towards improving manufacturing performance in a Jute bag manufacturing industry in Bangladesh. Specific objectives of this study are identification and reduction of major losses by using TPM tools and evaluation of the effectiveness by analyzing Overall Equipment Efficiency (OEE). The correlations between various TPM implementation dimensions and manufacturing performance improvements have been evaluated and validated by employing overall equipment effectiveness (OEE) in the jute bag plant. In this study TPM tools such as 5S, Autonomous Maintenance, Kobetsu Kaizen, Planned Maintenance and Education and Training have been implemented in the selected company. The equipment failure losses are reduced 3.85% through continuous improvement concept. The defect rate is reduced by 1.84% by taking preventive action. Most importantly it is observed that the OEE is improved from 7.42% i.e improved the productivity as well as improved the quality of product. Journal of Engineering Science 14(1), 2023, 137-149